2012
DOI: 10.1097/iio.0b013e31826861db
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in the Diagnosis and Management of Acute Idiopathic Maculopathy

Abstract: Acute idiopathic maculopathy (AIM), originally termed unilateral AIM, is a rare inflammatory disorder that typically affects young adults (mean age, 32 y; range, 15 to 45 y) and is characterized by acute, severe, unilateral vision loss preceded by a flu-like illness. Men and women are affected equally. Patients generally present with visual acuity of r20/200 and complain of central metamorphopsia and/or scotoma formation that is attributable to an exudative macular detachment. There may also be hypopigmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In conclusion, a unilateral acute idiopathic maculopathy case associated with more severe features than previously reported, including cystoid edema of the macula, flame shaped hemorrhages in the retina, and subretinal exudation, was reported. Depicting the unusual and rare features associated with a condition is necessary to help avoid misdiagnosis and unnecessary treatment as has been previously reported in cases of acute idiopathic maculopathy [7].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, a unilateral acute idiopathic maculopathy case associated with more severe features than previously reported, including cystoid edema of the macula, flame shaped hemorrhages in the retina, and subretinal exudation, was reported. Depicting the unusual and rare features associated with a condition is necessary to help avoid misdiagnosis and unnecessary treatment as has been previously reported in cases of acute idiopathic maculopathy [7].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent literature review, we have found that BALAD was commonly seen during the early stages of acute idiopathic maculopathy and additional cases have been reported since then. 2,4–14 I wonder whether the 4 cases that displayed serous retinal detachment at presentation also had BALAD on multimodal imaging.…”
mentioning
confidence: 99%